# The Roads We Take

### Problem

Dan Sitaru has kindly posted a problem of his at the CutTheKnotMath facebook page, and Leo Giugiuc added his solution (Solution 1) later on. Leo used an extremely powerful method they invented with Dan. The method has repeatedly proved useful in establishing various inequalities. It also worked for the problem at hand. This particular inequality admits an easier, though, less universal solution (Solution 2). This reminded me of "Shark" Dodson from O'Henry's "The Roads We Take" who after running from home came to a road fork. Some times later, he was telling his friend: "I came to a place one evenin' where the road forked and I didn't know which fork to take. I studied about it for half an hour, and then I took the left-hand." To which the friend replied, "Oh, I reckon you'd have ended up about the same."

Prove that, for $x,y,z\in(0,\infty)\;$ that satisfy $xyz=1\;$ the following inequality holds:

$x(x-3(y+z))^2+(3x-(y+z))^2(y+z)\ge 27.$

### Solution 1

Introduce $y+z=2s\;$ and $yz=p^2.\$ $s\;$ is positive by definition, $p\;$ is chosen to be positive. By the AM-GM inequality $s\ge p.\;$ Also, $\displaystyle x=\frac{1}{p^2}.$ In terms of $s\;$ and $p\;$ the inequality becomes

$\displaystyle \frac{(6sp^2-1)^2}{p^6}+\frac{2s(2sp^2-3)^2}{p^4}\ge 27.$

This ca be manipulated into

$f_{p}(s)=8s^3p^6+12s^2p^4+6sp^2-27p^6+1\ge 1.$

For any fixed $p,\;$ the function $f_{p}:\;[p,\infty)\rightarrow\mathbb{R} is strictly increasing, i.e., $f_{p}(s)\ge f_{p}(p).$ It will suffice to show that $f_{p}(p)\ge 0.\;$ But

$f_{p}(p)=8p^9-15p^6+6p^3+1=(p^3-1)^2(8p^3+1)\ge 0$

which completes the proof.

### Solution 2

Successively,

$\begin{align} x(x-3(y+z))^2&+(3x-(y+z))^2(y+z)\\ &=[x^3-6x^2(y+z)+9x(y+z)^2]\\ &\;\;\;+[9x^2(y+z)-6x(y+z)^2+(y+z)^3]\\ &=x^3+3x^2(y+z)+3x(y+z)^2+(y+z)^3\\ &=(x+y+z)^3\ge 27\sqrt[3]{xyz}=27, \end{align}$

by the AM-GM inequality.

### Inequalities with the Product of Variables as a Constraint

- An Application of Schur's Inequality II $\left(\sum (x^4+y^3+z) \ge \sum \left(\frac{x^2+y^2}{z}\right)+3\right)$
- Problem 1 From the 2016 Pan-African Math Olympiad $\left(\displaystyle \sum_{cycl}\frac{1}{(x+1)^2+y^2+1}\le\frac{1}{2}\right)$
- A Cyclic But Not Symmetric Inequality in Four Variables $\left(\displaystyle 5(a+b+c+d)+\frac{26}{abc+bcd+cda+dab}\ge 26.5\right)$
- Problem 2, the 36th IMO (1995) $\left(\displaystyle \frac{1}{a^3(b+c)}+\frac{1}{b^3(c+a)}+\frac{1}{c^3(a+b)}\ge\frac{3}{2}\right)$
- An Inequality with Two Cyclic Sums $\left(\displaystyle \sum_{cycl}(a+\sqrt[3]{a}+\sqrt[3]{a^2})\ge 9\sum_{cycl}\frac{1}{1+\sqrt[3]{b^2}+\sqrt[3]{c}}\right)$
- The Roads We Take $(x(x-3(y+z))^2+(3x-(y+z))^2(y+z)\ge 27)$
- Long Huynh Huu's Inequality and Solution $\left(\displaystyle \sum_{i=1}^n\arctan x_i\le (n-1)\frac{\pi}{2}\right)$
- An Inequality with Integrals $\left(\Omega=\int_0^u\frac{u^4+7x^3-25x^2+37x+4}{x^4-3x^3+5x^2-3x+4}dx,\;\Omega(a)+\Omega(b)+\Omega(C)\ge3+5\ln\prod_{cycl}(1+a^2)\right)$
- An Inequality with Cycling Sums $\left(\displaystyle\sum_{cycl}(x^4+y^3+z)\ge \sum_{cycl}\frac{x^2+y^2}{z}+3\right)$
- Two Products: Constraint and Inequality $\left(\displaystyle\prod_{k=1}^n(1+a_k)\ge 2^n\right)$
- Leo Giugiuc's Cyclic Inequality with a Constraint $\left(\displaystyle a^3+b^3+c^3+\frac{16}{(a+b)(b+c)(c+a)}\ge 5\right)$

|Contact| |Front page| |Contents| |Algebra|

Copyright © 1996-2018 Alexander Bogomolny69119316